Revaluating CUNA Places (CUltural Place of High Relevance for NAture): Rome as a Multifaced Example of Outstanding Values and Potentials - Giulia Caneva; Zohreh Hosseini; Flavia Bartoli; Giulia Capotorti; Fabio Attorre; Carlo Blasi (Land)
The Global Frameworks for Enhancing Natural and Cultural Capital, as expressed in the Charter of Rome (2014), have relevant importance in the broader context of sustainable development goals (SDGs). The intricate connection between cultural and natural heritage emerges in various documents from UNESCO, IUCN, and ICOMOS; however, the categories and methods for their assessment are not completely defined. Evolving from the concept of “mixed properties” used in the UNESCO definitions, we introduce the concept of CUNA places: cultural places of high relevance for nature. It provides a methodological tool for identifying and typifying these places based on their values, attributes, and significance. Then, we propose definitions and categories for three different CUNA typologies, comprising 16 categories, considering both tangible and intangible heritage. We also provide a preliminary application to the city of Rome, where a rich historical heritage intersects with outstanding natural values. All the typologies and categories of CUNA places are present in Rome, and further analysis could show the multifaced aspects represented here. On a broader scale, such an application offers the opportunity to enhance the heritages that could be valorized, strengthening the territorial identity, promoting sustainable development, and generating income for conservation efforts.